A Rare Complication During Transcatheter Closure of Double Atrial Septal Defects With Incomplete Cor Triatriatum Dexter: A Case Report - Chen, Ping-Hong; Liu, Yi-Ching; Dai, Zen-Kong; Chen, I-Chen; Lo, Shih-Hsing; Wu, Jiunn-Ren; Wu, Yen-Hsien; Hsu, Jong-Hau (Frontiers in Cardiovascular Medicine, 2022)
The cor triatiatum dexter is an embryologic remnant derived from the right atrium and totally separate from the right atrium. An incomplete cor triatiatum dexter (iCTD) means a partially obstructive remnant at the right atrium. It is usually formed by a remnant of the Eustachian valve (EV), Thebesian valve (ThV), or Chiari network (CN). This anatomic variant is usually asymptomatic but is often associated with other heart abnormalities including atrial septal defects (ASDs), and has the potential to hamper percutaneous heart procedures such as electrophysiological study or ASD closure. Herein, we report a rare complication, transient heart ischemia, in transcatheter closure of double ASDs in a 55-year-old woman with EV. This rare complication was thought to be caused by coronary sinus obstruction during device placement. The ischemic change was resolved spontaneously after we withdrew the device. For a second attempt, we adjusted the position of the device to avoid coronary sinus obstruction under transesophageal echocardiogram guidance and the device was smoothly deployed in a good position with a minimal residual shunt. This case suggests that anatomy details in percutaneous heart procedures are important, and this rare and dangerous complication, heart ischemia, should be identified immediately during the procedure.